Factor Analysis of Husband Involvement in Domestic Work - Tjubandrio, Francesca; Yuwanto, Listyo; Rahaju, Soerjantini (Faculty of Psychology, Universitas Surabaya, 2010)
A harmonious marriage requires cooperation and commitment between a husband and a wife in dealing with domestic affairs. Both a husband and a wife, who have been committed to a mar- riage, should participate in domestic work. A husband who gets involved in domestic work is driven by various factors. The purpose of this study is to explore the factors that encourage hus- band involvement in the domestic work. Data were obtained from 148 male respondents (23-40 years old) using interview and questionnaire. The respondents have been married and involved in domestic work. The result shows that there are six major factors that encourage husband in- volvement in domestic work. Pernikahan yang harmonis membutuhkan kerjasama dan komitmen suami istri dalam men- gurus rumah tangga. Laki-laki dan perempuan dalam rumah tangga, keduanya haruslah ikut serta dalam kerja domestik rumah tangga. Laki-laki yang mau terlibat dalam kerja domestik rumah tangga didorong oleh berbagai faktor. Tujuan penelitian ini adalah mengeksplorasi faktor-faktor yang mendorong keterlibatan laki-laki dalam kerja domestik rumah tangga. Data diperoleh melalui wawancara, pembagian skala kepada 148 responden penelitian (23- 40 tahun) yang telah berkeluarga dan terlibat dalam kerja domestik rumah tangga. Hasil pe- nelitian mengungkapkan bahwa terdapat enam faktor besar yang mendorong laki-laki terli- bat dalam kerja domestik keluarga.